Learning Stability in Economies with Heterogenous Agents - Seppo Honkapohja; Kaushik Mitra (Center for Economic Studies and ifo Institute (CESifo), 2002)
An economy exhibits structural heterogeneity when the forecasts of different agents have different effects on the determination of aggregate variables. Various forms of structural heterogeneity can arise and we study the important case of economies in which agents' behavior depends on forecasts of aggregate variables and show how different forms of heterogeneity in structure, forecasts, and adaptive learning rules affect the conditions for convergence of adaptive learning towards rational expectations equilibrium. Results are applied to the market model with supply lags and a New Keynesian model of interest rate setting.
Keywords: C62; D83; E37; 330; adaptive learning; expectations formation; stability of equilibrium; market model; monetary policy.